Adsorption and Desorption of Major Gases on Some Clays Obtained by Heating Tobacco at Certain Temperatures - YALÇINKAYA, Zeki; CEYLAN, Hasan (MAS Journal of Applied Sciences, 2022)
The tobacco roasting-process was carried out and a study was carried out on the composition ofthe gases released during this process. It has been determined that the amounts of substances obtained fromthe studied tobacco are generally less than the amounts of substances obtained in the literature. The volatilegases formed during this roasting were passed over some clay minerals and adsorbed on them. The adsorbedcomponents were desorbed by diethyl ether extraction. Adsorption and desorption analyzes wereinvestigated by GC and TG techniques. The components released during the tobacco-roasting process werefirst directly obtained and analyzed by gas chromatography. Then, the adsorbing efficiency to clay for eachof the components in the vapors from tobacco was calculated by comparing the amount of the componentretained in the absence of adsorbent with the amount retained after the component was passed over theadsorbent. The structure of the clay samples used as adsorbent was investigated by chemical analysis andDTA techniques. The adsorption efficiencies are discussed with the physical properties of the clays, theaffinities of the volatile components, and their adsorption efficiency. Most of the volatiles adsorbed on theadsorbents were recovered by diethyl ether extraction. Especially benzaldehyde, propionic acid, furfurylalcohol, 3-methylbutanoic acid and nicotine were recovered with good yield.